Adaptive resilience in family business during and post-crisis: the mediating role of improvisation - Mchiri, Ali (Piccola Impresa / Small Business, 2023)
Purpose. This study attempts to answer the calls for a better conceptualization of the resilience of firms during times of uncertainty. In this paper, we conceptualize resilience as an adaptive process where entrepreneurs constantly learn from external events and use available resources to increase their capacity to respond effectively during and post-crisis. More specifically, we suggest that actors in family firms should tap into their psychological resources, including grit and self-efficacy, to strengthen their adaptive resilience through improvisation. Methodology: We offer several propositions and a conceptual model for empirical testing. Findings: We extend prior conceptualizations emphasizing the need to understand better the resilience construct. More specifically, there is a paucity of management inquiries investigating adaptive resilience as a dynamic and responsive process to changes in the operating environment. The findings from the empirical testing for the proposed relationships would be important in providing a thorough conceptualization of the resilience construct in the business and management field. Practical and social implications: Given the vital role that SMEs and small family firms play in our economies, it is crucial to understand the determinants and the factors influencing the resilience of these businesses. To this extent, this study encourages organizational researchers and practitioners to investigate intangible factors, including psychological resources and their role in enhancing resilience at the individual and firm levels. However, to increase resiliency, we argue that small family firms should emphasize and prioritize preparedness over improvisation. Originality: This study sheds light on the need to understand how, individual factors, including psychological resources, affect resiliency at the firm level through the role of improvisation, within the family business context.